(3GdhLjR aj YbhO GdJfejI GdJbfjI (B/s - (3LGHQ, YHO GdQDhas ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2005)
(3GdJfXje GdbGfhfj dfbd GdYdhe GdJWHjbjI(B((3JcfhdhLjG(B): (3GdLghO GdOhdjI dJfXje fbd GdYdhe GdJWHjbjI, GdOjHGLI hCgOGa GdJbfjf hCUhdg GdYGeI, GdJYGQja hfWGb GdJWHjb, GdVeGfGJ hGdeSDhdjGJ hGdJYgOGJ, eYGedI NGUI ddOhd GdfGejI, GdJYGhf GdOhdj aj eLGd fbd GdYdhe(B. (3YbO fbd GdYdhe GdJWHjbjI(B: (3HjGf GdYbO, YbO JSdje ,GfJGL, YbO GdeSGYOI GdafjI, YbO JSdje GdeaJGM(B: (3GfTGA GdYbO, GdJRGeGJ GdebGhd, GdJRGeGJ GdYejd, GdJNda Yf GdJfajP hGdeSDhdjI, GSJMGdI GdJfajP hJZjjQ XQha GdYbO, GdbGfhf GdhGLH GdJWHjb haV GdefGRYGJ(B.s
(3GdeQGLY U(B.257s
Keywords: (3GdYbhO GdJLGQjIs; (3GdYbhO(B- (3GdbGfhf GdeOfjs